THE EFFECT OF E-SERVICE QUALITY ON CUSTOMER SATISFACTION OF CASH RECYCLING ATM USERS WITH TECHNOLOGICAL OPTIMISM AS A MODERATING VARIABLE - Nurida Dhatin Afiza Rachman; Ratih Hendayani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
In business organizations, there has been an increase in the use of information technology and rapid technological developments, including in the banking industry. Most banks have implemented technology-based self-service solutions to overcome barriers related to time, distance, and communication. One of these solutions is the Automated Teller Machine (ATM). The object of this study is the BCA Cash Recycling ATM. The purpose of this study is to explain the relationship between reliability, security, convenience, functionality, responsiveness, and customer satisfaction in Cash Recycling ATM users, including technological optimism as a moderator. This study used quantitative methods with data analysis techniques, using partial least squares (PLS) structural equation modeling (SEM). The number of samples used in this study was 114 Bank BCA customers domiciled in Bandung City who had used BCA Cash Recycling ATMs to conduct banking transactions. The findings of this study show a positive and significant relationship between convenience and customer satisfaction. However, reliability, security, functionality, and responsiveness did not have a significant effect on customer satisfaction. Technological optimism did not have an interaction effect (moderation) on the relationship between the five factors of e-service quality on SST and customer satisfaction.